PELATIHAN PENGOLAHAN UDANG REBON MENJADI SUMPIA BERSTANDAR HALAL SEBAGAI UPAYA PENGUATAN UMKM DI DESA SUKA MAJU - Zaifatur Ridha; Syarifah; Aisyah Nurcahyani; Muhammad Ikhsan Nasution; Siti Patimah; Halimatun Sakdiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve community knowledge and skills in utilizing local food resources, specifically rebon shrimp, through training in processing it into halal-standard sumpia products. The activity was conducted in Suka Maju Village, Tanjung Pura District, using a participatory method consisting of socialization, training, hands-on practice, and evaluation. The participants were local residents, particularly housewives and small business actors. The results showed an increase in participants' understanding and skills in processing rebon shrimp into value-added products. Prior to the training, most participants were unfamiliar with the processing techniques. After the training, they were able to understand the production process and showed interest in developing local-based businesses. The program also raised awareness of simple business management and halal production standards. Therefore, this training contributes to strengthening MSMEs and empowering the local economy.